Enhancing Mediation Skills through Legal Counseling for Indonesian Citizens in Thailand: A Case Study of PCIM Thailand: Peningkatan Keterampilan Mediasi melalui Penyuluhan Hukum bagi Warga Negara Indonesia di Thailand: Studi Kasus pada PCIM Thailand - Tinuk Dwi Cahyani; Saputra, Fauzan (Jurnal Dedikasi Hukum, 2025)
The objective of mediator legal counseling is to facilitate the resolution of legal issues encountered by Indonesian citizens and cadres residing in Thailand. However, PCIM Thailand lacks specialized expertise in out-of-court settlement or mediation. In this context, mediation is employed to reconcile disparities in bargaining power between conflicting parties to reach an agreement. The mediator's role is primarily focused on addressing the issues articulated by the conflicting parties. The counseling approach encompasses preparation, elucidation of the mediator's role and function, task allocation, and a question-and-answer session. All participants in this program observed a mediation simulation conducted by each group. Each group assumed the role of mediator and facilitated communication between both parties to resolve the dispute. The concept of "being in the middle" necessitates that the mediator maintain neutrality and impartiality, refraining from favoring either party in conflict. Through this legal service, participants acquired a more comprehensive understanding of the concepts discussed in mediation, including the mediator's role, negotiation strategies, and constructive conflict management techniques. This outreach has at least had an impact on PCIM members' confidence in handling social conflicts. Furthermore, their mediation skills serve as a liaison between PCIM and local communities and formal institutions. However, PCIM members still lack a basic understanding of the law, putting them at risk of committing procedural violations or misinterpreting legal arguments.   Tujuan dari penyuluhan hukum mediator adalah untuk memfasilitasi penyelesaian permasalahan hukum yang dihadapi oleh WNI dan kader yang berada di Thailand. Namun, PCIM Thailand tidak memiliki keahlian khusus dalam penyelesaian atau mediasi di luar pengadilan. Dalam konteks ini, mediasi digunakan untuk mendamaikan kesenjangan daya tawar antara pihak-pihak yang berkonflik untuk mencapai kesepakatan. Peran mediator terutama terfokus pada penyelesaian permasalahan yang diutarakan oleh pihak-pihak yang berkonflik. Pendekatan konseling meliputi persiapan, penjelasan peran dan fungsi mediator, pembagian tugas, dan sesi tanya jawab. Seluruh peserta program ini mengamati simulasi mediasi yang dilakukan masing-masing kelompok. Masing-masing kelompok berperan sebagai mediator dan memfasilitasi komunikasi antara kedua belah pihak untuk menyelesaikan perselisihan. Konsep “berada di tengah” mengharuskan mediator menjaga netralitas dan imparsialitas, tidak memihak salah satu pihak yang berkonflik. Melalui layanan hukum ini, peserta memperoleh pemahaman yang lebih komprehensif tentang konsep-konsep yang dibahas dalam mediasi, termasuk peran mediator, strategi negosiasi, dan teknik manajemen konflik yang konstruktif. Penyuluhan ini setidakya berdampak pada kepercayaan diri  anggota PCIM dalam menangani konflik sosial. Selain itu, kemampuan mediasi juga berfungsi sebagai penghubung antara PCIM dengan komunitas masyarakat setempat maupun lembaga formal. Akan tetapi, anggota PCIM tetap kurang memiliki pemahaman dasar hukum, sehingga berisiko melakukan pelanggaran prosedur atau kesalahan menafsirkan dalil hukum.